2015
DOI: 10.1002/cmdc.201402477
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Guided Design, Synthesis, and Biological Evaluation of Quinoxalinebisarylureas as FLT3 Inhibitors

Abstract: Activating mutations of FMS-like tyrosine kinase 3 (FLT3) are present in ∼30 % of patients with acute myeloid leukemia (AML) and are associated with poor prognosis. Point mutations in the tyrosine kinase domain (TKD) are observed as primary mutations or are acquired as secondary mutations in FLT3 with internal tandem duplications (ITDs) after treatment with tyrosine kinase inhibitors (TKIs). Although dozens of potent inhibitors against FLT3 ITD have been reported, activating TKD point mutations, especially at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…of 4,5-dimethylbenzene-1,2-diamine ( 7 ) to the reaction solution and irradiated it with visible light for 12 h at room temperature ( Scheme 3 ). Not surprisingly, we obtained the corresponding 6,7-dimethyl-2-phenylquinoxaline ( 8 ), which is a biologically active FLT3 inhibitor, 15 in 65% yield as a product in this unprecedented photoredox copper catalyzed one-pot process ( Scheme 3 ). We did not observe the formation of 3-phenylquinoxalin-2-ol as a product in the current photoredox method, which was previously reported as a key product under strong basic conditions.…”
Section: Resultsmentioning
confidence: 97%
“…of 4,5-dimethylbenzene-1,2-diamine ( 7 ) to the reaction solution and irradiated it with visible light for 12 h at room temperature ( Scheme 3 ). Not surprisingly, we obtained the corresponding 6,7-dimethyl-2-phenylquinoxaline ( 8 ), which is a biologically active FLT3 inhibitor, 15 in 65% yield as a product in this unprecedented photoredox copper catalyzed one-pot process ( Scheme 3 ). We did not observe the formation of 3-phenylquinoxalin-2-ol as a product in the current photoredox method, which was previously reported as a key product under strong basic conditions.…”
Section: Resultsmentioning
confidence: 97%
“…It is the most common mutated gene in AML (was cloned in 1993 ) and has been expressed in most tissues including hematopoietic organs (spleen and bone marrow), prostate, ovary, heart, lung, kidney, and placenta . FLT3 structure is composed of an N‐terminal extracellular ligand binding domain with five immunoglobulin‐like motifs, a transmembrane domain followed by an intracellular juxta‐membrane domain, and a C‐terminal tyrosine kinase domain .…”
Section: Quinoxalines As Kinase Inhibitors and Potential Anticancer Amentioning
confidence: 99%
“…In 2009, Chao et al identified bisarylurea and they were evaluated as a uniquely potent and selective FLT3 inhibitor. In 2015, Göring et al designed a set of diverse quinoxaline‐bisarylureas, which were profiled in an FLT3 kinase activity assay. Their study used the pharmacophore features of different known inhibitors as a starting point for a new optimization algorithm for type II TKIs, starting from an in silico library pharmacophore search and induced‐fit docking in the known FLT3 structure.…”
Section: Quinoxalines As Kinase Inhibitors and Potential Anticancer Amentioning
confidence: 99%
See 1 more Smart Citation
“…Ureas, especially those functionalized with a heterocyclic moiety, are widely applied in drug design 1,2 and demonstrate antimicrobial, 3,4 antimalarial, [5][6][7] antivirus, 8 and anticancer [9][10][11][12][13][14] activities. Moreover, ureas act as kinase (LIM, VEGFR2, FGFR, FLT3) inhibitors, [15][16][17][18][19][20] they control gastric acid secretion, 21 and are used as plant growth regulators. 22,23 All known syntheses of ureas employ either various organic (in particular, chlorinated) solvents or heavy metals.…”
Section: Introductionmentioning
confidence: 99%